Enrollment, Childbearing Motivations, and Intentions of Couples in the Creighton Model Effectiveness, Intentions, and Behaviors Assessment (CEIBA) Study - Stanford, Joseph B.; Porucznik, Christina A. (Frontiers in Medicine, 2017)
Context: The Creighton Model FertilityCare System (CrM) is a standardized approach for educating women about the biomarkers of their fertility. Couples can use this information for timing intercourse during “fertile” or “infertile” days in order to try to conceive or to avoid pregnancy. Objectives: The study of Creighton Model Effectiveness, Intentions, Behaviors Assessment (CEIBA) was conducted to assess fertility motivations, intentions, fertility-related sexual behaviors, and their impact on effectiveness to avoid and to conceive among new users of the CrM. This paper reports enrollment baseline characteristics. Settings and design: We conducted this prospective cohort study at 17 CrM FertilityCare Centers; 16 in the USA and one in Toronto, Canada. Materials and methods: Couples who were new or returning users of the CrM were eligible. Couples who were initially trying to conceive or had a history of subfertility were excluded. Couples were enrolled and followed prospectively by their CrM instructors, and also by CEIBA study staff. They completed baseline questionnaires. Results: 1133 new couples were assessed; 1090 (96%) couples were screened; 429 (39%) couples were eligible; 305 women (71%) and 290 (95%) male partners were enrolled. The majority of women was engaged (39%) or married (51%), college graduates (77%), Caucasian non-Hispanic (80%), and Roman Catholic (80%). The most common reasons for learning CrM (women) were to use a natural method for family planning (91%), for moral/ethical/religious reasons (70%), the lack of side effects (71%), or insight into the menstrual cycle and fertility (62%). Women and men intended to have a mean of 3 and 2 additional children, respectively. Of women, 21% intended to have a child within a year, and 60% between 1 to 3 years. The mean positive childbearing motivation score was 3.3 for both women and men (range 1-4, with 4 being most positive). Conclusion: Couples beginning use of the CrM to avoid pregnancy have high levels of motivation, desire, and intention for future childbearing. The CEIBA study has prospective measures of desires, intentions, and sexual/fertility behaviors for up to one year. We will assess the impact of desires, intentions and behaviors on the pregnancy rates among these couples.